Tuberculosis: Past, present and future of the treatment and drug discovery research - Ameya D. Bendre; Peter J. Peters; Janesh Kumar (Elsevier, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Despite decades of research driving advancements in drug development and discovery against TB, it still leads among the causes of deaths due to infectious diseases. We are yet to develop an effective treatment course or a vaccine that could help us eradicate TB. Some key issues being prolonged treatment courses, inadequate drug intake, and the high dropout rate of patients during the treatment course. Hence, we require drugs that could accelerate the elimination of bacteria, shortening the treatment duration. It is high time we evaluate the probable lacunas in research holding us back in coming up with a treatment regime and/or a vaccine that would help control TB spread. Years of dedicated and focused research provide us with a lead molecule that goes through several tests, trials, and modifications to transform into a 'drug'. The transformation from lead molecule to 'drug' is governed by several factors determining its success or failure. In the present review, we have discussed drugs that are part of the currently approved treatment regimen, their limitations, vaccine candidates under trials, and current issues in research that need to be addressed. While we are waiting for the path-breaking treatment for TB, these factors should be considered during the ongoing quest for novel yet effective anti-tubercular. If these issues are addressed, we could hope to develop a more effective treatment that would cure multi/extremely drug-resistant TB and help us meet the WHO's targets for controlling the global TB pandemic within the prescribed timeline.